Analysis of halal tourism potential from the perspective of a holistic travel experience in Banten province - Irwan Sukmawan; Muhammad Angga Anggriawan; Hadi Kurniawanto (Jurnal Pariwisata Pesona, 2024)
This research explores the factors that affect tourist satisfaction in halal tourism, with a particular emphasis on Banten Province. The results indicate that although halal accommodations are necessary, they are seen more as a fundamental requirement than a significant driver of satisfaction. Conversely, the presence and quality of halal facilities and services are key to elevating the overall tourist experience. Additionally, the attitudes and behaviors of residents, as well as the destination's ability to provide a break from daily life, greatly influence tourist satisfaction. Religiosity stands out as a crucial moderating factor, enhancing the positive impact of halal accommodations and facilities on satisfaction. For tourists with strong religious beliefs, the adherence of services to Islamic principles is vital. This study highlights the importance of incorporating religiosity into the development and marketing of tourism products to maximize the potential of halal tourism, especially in areas like Banten Province. By focusing on comprehensive travel experiences that address both spiritual and practical needs, destinations can increase tourist satisfaction, foster loyalty, and encourage positive word-of-mouth, thereby supporting sustainable growth in the halal tourism industry.